Measurement of the prompt-production cross-section ratio σ(χc2)/σ(χc1) in pPb collisions at √sNN=8.16 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2021)
This article reports the first measurement of prompt χc1 and χc2 charmonium production in nuclear collisions at Large Hadron Collider energies. The cross-section ratio σ(χc2)/σ(χc1) is measured in pPb collisions at √sNN=8.16 TeV, collected with the LHCb experiment. The χc1,2 states are reconstructed via their decay to a J/ψ meson, subsequently decaying into a pair of oppositely charged muons, and a photon, which is reconstructed in the calorimeter or via its conversion in the detector material. The cross-section ratio is consistent with unity in the two considered rapidity regions. Comparison with a corresponding cross-section ratio previously measured by the LHCb Collaboration in pp collisions suggests that χc1 and χc2 states are similarly affected by nuclear effects occurring in pPb collisions.